Are Patient Reported Outcome Measurement Information System scales responsive in patients attending physical therapy with foot and ankle diagnoses? - Neville, Christopher; Baumhauer, Judith; Houck, Jeff (Physiotherapy Theory & Practice, 2023)
Patient-reported outcomes (PROs) have been used to provide insight into the patient experience while uncovering an opportunity to improve patient care. Current studies document responsiveness of outcomes using the Patient Reported Outcome Measurement Information System (PROMIS) for a variety of orthopedic problems but are not specific to a physical therapy interval of care. The main purpose of this study was to examine responsiveness of the PROMIS Physical Function (PF) and Pain Interference (PI) scales across an interval of care for physical therapy in patients with foot and ankle conditions. Adult records (299 records, averaged 45.1 ± 15.4 years; 61% female) were assessed. Comparisons between pre- and post-physical therapy intervals of care were evaluated using a repeated-measures ANOVA, and the effect size was reported using Cohen's d. PROMIS PF scores significantly improved from 38.5 ± 8.8 to 45.2 ± 9.1 (6.6; p <.001; Cohen's d = 1.0). PROMIS PI scores significantly improved from 56.8 ± 8.8 to 53.0 ± 9.8 (−3.8; p <.001; Cohen's d = 0.52). The person-centered PROMIS PF and PI outcome measures were responsive to change following an interval of care in physical therapy for a large sample of orthopedic patients with foot and ankle diagnoses. The magnitude of change was dependent on starting score and diagnosis.